Analysis of the Influence Work Enthusiasm at PT. Lembaga Keuangan Mikro Demak Sejahtera - Niamul Haq, Ahmad Kevin; Sijabat, Rauly; Dharmaputra, Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to investigate how Workload, Work Communication, and Work Environment impact Employee Work Enthusiasm at PT. Demak Sejahtera Microfinance Institution in Demak city. The research employed a nonprobability sampling technique using a Saturated sampling method, with a sample size of 72 employees selected from all employees working at microfinance institutions in Demak. Data analysis was conducted using the Multiple Linear Regression technique with the Statistical Package for the Social Sciences (SPSS). The findings and discussion revealed that Workload and Work Communication did not individually have a significant positive influence on Employee Work Enthusiasm. However, the Work Environment significantly and positively influenced Employee Work Enthusiasm at PT. Lembaga Keuangan Mikro Demak Sejahtera